Checklist of pasture species at Biratnagar, Eastern Nepal - Niroula, Bhabindra; Dangi, Yam Prakash; Shah, Poonam; Jha, Sasinath (Nepalese Journal of Biosciences, 2019)
Pasture species of Biratnagar area were seasonally observed during 2018. A total of 77 species including monocot grasses (27) nonlegumes forbs (43), and legumes (7) were recorded. Seasonally, summer had maximum number of species (73), followed by rainy (64 species) and winter (53 species). Occasional and scarce native grasses were replaced by unpalatable and invasive species. Desmostachya bipinnata (graminoid) and Indigofera linifolia (legume) were the scarcely found species.